Krajobraz pod lasem. O Rhizopolis Joanny Rajkowskiej - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article contains an analytical and interpretative study of the poetics of two recent art installations by Joanna Rajkowska.